Alopecia with Vitamin D-Dependent Rickets Type 2 A: A Case Report - Bin Rubaian NF; Al-Awam BS; Aljohani SM; Almuhaidib SR (Dove Medical Press, 2024)
Nouf F Bin Rubaian,1 Bashayer S Al-Awam,2 Samah M Aljohani,1 Serene R Almuhaidib3 1Department of Dermatology, King Fahad University Hospital, Al Khobar, Saudi Arabia; 2Department of Pediatrics, King Fahad University Hospital, Al Khobar, Saudi Arabia; 3Department of Dermatology, Dammam Medical Complex, Dammam, Saudi ArabiaCorrespondence: Serene R Almuhaidib, Department of Dermatology, Dammam Medical Complex, Dammam, Saudi Arabia, Email SereneAlmuhaidib@gmail.comAbstract: Vitamin D-dependent rickets type II (VDDR2) is a rare inherited autosomal recessive disorder wherein the genetic mutation results in a defect in the vitamin D receptor (VDR), thus leading to target resistance to 1.25-dihydroxy vitamin D. This results in hypocalcemia, hypophosphatemia, secondary hyperparathyroidism, and rickets. We report a case of a four-year-old female child with diffuse alopecia starting 2 weeks after birth, along with frontal bossing, hypoplastic teeth, and an unusual presentation of multiple skin-colored papules over the back. Genetic testing confirmed vitamin D-dependent rickets type 2A.Keywords: pseudovitamin D-deficiency, rickets-alopecia syndrome, hypocalcemic vitamin D-resistant rickets, genetic mutation